INFLUENCE OF HEALTH AEROBICS ON THE DEVELOPMENT OF ENDURANCE IN WOMEN AGED 25-30 - Mirjamolova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
The article deals with the problems of health promotion and development of physical qualities of women. The age of 25-30 years is characterized by active labor activity. In this age interval, there are slow, but steady, declines in a number of indicators of the level of a person’s physical potential: from a slowdown in metabolism to a decrease in physical activity.